Multi-interval-uncertainty constrained robust dispatch for AC/DC hybrid microgrids with dynamic energy storage degradation. (15th October 2018) - Qiu, Haifeng; Gu, Wei; Pan, Jing; Xu, Bin; Xu, Yinliang; Fan, Miao; Wu, Zhi
Highlights: Linearized dynamic energy storage degradation model is proposed. Influences of state of charge and charge rate on degradation are investigated. All unit states are coordinated to achieve the optimal operation. Uncertainty budget is rationally divided according to distribution probabilities. Nested column-and-constraint generation algorithm is adopted for solution. Abstract: Multiple uncertainties have brought great challenges to the optimal dispatch of microgrids (MGs). Considering the uncertainties of renewable energy generation and load power in AC/DC hybrid MGs, this paper proposes a multi-interval-uncertainty (MIU) constrained robust dispatch model, in which the uncertainty budget is rationally divided according to the distribution probabilities to improve the over-conservativeness of traditional robust models. To understand how the charge/discharge rate and the state of charge influence the degradation of energy storage (ES), a dynamic energy storage degradation (DESD) model is also proposed to accurately calculate the degradation cost of ES. The nonlinear DESD model is linearized by the surface linearization and big-M methods. To address the min–max-min robust model with a mixed-integer recourse problem, a nested column-and-constraint generation algorithm is adopted to quickly obtain the minimum operating cost in the worst-case scenario. The rationality and validity of the MIU constrained robust dispatch model, the DESD model, and the solving method are verified in comparative case studies.